Making It Real: The Benefits of Workplace Learning in Upper-Secondary VET Courses - Cain Polidano; Domenico Tabasso (Institute for the Study of Labor (IZA), 2013)
In OECD countries, 'real world' upper-secondary vocational education and training (VET) programs are used to engage less academically oriented youth in learning, while helping to prepare them for post-school work and/or further training. In general terms, VET programs with high employer involvement, such as apprenticeship schemes, are considered to be superior to classroom-based VET programs that are typically found in many English-speaking countries. In this study, we examine outcomes from a potential 'third way': classroom-based VET with a short-term structured workplace learning component. Using propensity score matching and PISA data linked to information from the Longitudinal Survey of Australian Youth, we find time in workplace learning is associated with higher school completion rates and better employment transitions.
Keywords: I20; J01; 330; educational economics; vocational education and training; workplace learning